2014
DOI: 10.1039/c3nj00895a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and crystal structures of a series of Schiff bases: a photo-, solvato- and acidochromic compound

Abstract: Seven Schiff base derivatives of 4-dimethylamino-trans-cinnamaldehyde were synthesized in good yield.The structures of all new derivatives were established by IR, 1 H, 13 C NMR and HRMS experiments and three of them were corroborated by X-ray diffraction studies. Analysis of the supramolecular structures evidenced the presence of strong intermolecular hydrogen bonds (O-HÁ Á ÁN) which promote the formation of molecular chains. The linear properties of this series of chromophores were investigated by UV-Vis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 66 publications
(19 reference statements)
0
20
0
Order By: Relevance
“…The Lippert-Mataga equation (shown in Supplementary Material) is widely used to evaluate the dipole moment changes of the dyes with photoexcitation [ 33 , 34 ]; the emission of the chromophores, especially, is strongly dependent on solvent polarity. As shown in Figure 2 , the Lippert-Mataga plots exhibit a linear behavior; this means no specific interaction exists between the solvent and the chromophores, except for the polarizability as modeled [ 35 , 36 ]. The slop of the fitting line is related to the dipole moment change between the ground and excited states ( μ e − μ g ).…”
Section: Resultsmentioning
confidence: 99%
“…The Lippert-Mataga equation (shown in Supplementary Material) is widely used to evaluate the dipole moment changes of the dyes with photoexcitation [ 33 , 34 ]; the emission of the chromophores, especially, is strongly dependent on solvent polarity. As shown in Figure 2 , the Lippert-Mataga plots exhibit a linear behavior; this means no specific interaction exists between the solvent and the chromophores, except for the polarizability as modeled [ 35 , 36 ]. The slop of the fitting line is related to the dipole moment change between the ground and excited states ( μ e − μ g ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar bathochromic shifts in substrate absorbance have been observed for other iminium ion-forming organocatalysts 31 and enzymes. 26 , 32 Spectroscopic titration studies with a Schiff-base adduct of 1a in organic solvents 33 suggest that the species formed between 1a and Lys-167 is likely protonated. Additionally, after chemically reducing DERA-MA in the presence of 1a with NaBH 3 CN, ESI-MS analysis revealed that compared to unmodified DERA-MA, the observed major peak increased by + 117 Da, corresponding to the covalent modification of the protein with one molecule of the reduced Schiff-base adduct of 1a (calcd.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Single crystal X-ray diffraction (SCXRD) confirmed that the imine crystal structure consists of two diaminothiophene units and one ethylenedioxythiophene group, and indicating also the E conformation of the heteroatom double bond. Sanchez et al [ 43 ] described the synthesis of Schiff bases and their photochromic behavior as an effect of intermolecular hydrogen bond formation. It was demonstrated that only Schiff’s base derivatives of phenylglycinol showed photochromism in the solid state.…”
Section: Introductionmentioning
confidence: 99%